PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN PSIKIS DALAM RUMAHH TANGGA - Markuat Markuat (Sekolah Tinggi Pariwisata Mataram, 2020)
Domestic Violence (domestic violence) had become a commonagenda in recent decades. Facts show that domestic violence disproportionatelyaffects large enough for children as victims. Violence against children is not a rarecase in the community. Children have been taught since childhood to be obedientand disobedient to parents in a violent manner. Parents in applying discipline to achild does not always pay attention to the existence of the child as a human being,a child is given the rules of the parents who do not appreciate the rational andwithout the presence of a child with all of his rights, such as the right of childrento play. The research that have done is a normative research of law which isfocused on the norm and also the object of law as the main data, they getting fromrule and books that consist of the rule, that had to fine the truth from the researchthat have done. The writter made a research in DIY Police. The result of this studywere: (1) Implementation of legal protection of children as victims of domesticviolence can be done in two ways, namely the efforts of non-penal and penaleffort. Non-penal effort done by a preemptive and preventive, while the effortsmade by the penal repressive actions by the police DIY after psychologicalviolence within the domestic sphere occur and are reported to the police.(2)Constraints faced by the police in the implementation of the legal protection ofchildren as victims of psychological violence in the household, namely: (a) Thedifficulty of finding strong evidence of a child victim of psychological violence,in this case the question is about how to form of psychological violence. (b) Thedifficulty to distinguish children who are experiencing emotional violencecommitted by family members in a household setting. A child who isexperiencing violence usually has a psychological fear to reveal the problems theyexperienced as a result of the act of the perpetrator. (c) The number of childvictims of psychological violence to the people who shut themselves in theirenvironment and also includes the police or to Child Protective Services. (d) Thedelay in the reports of family members in household, and also includes reportsfrom neighbors who saw or hear direct actions and words of the perpetrators ofsuch violence